Analisis Faktor-Faktor Kesulitan Belajar Siswa pada Mata Pelajaran Ekonomi di Kelas XI IPS SMA Negeri 1 Mollo Selatan - Kase, Stefen; Nggandung, Yeheskial; Loe, Andri Paulus (Journal Economic Education, Business and Accounting, 2024)
this research aims to determine the factors that cause students to have difficulty learning economic in class XI IPS SMA Negeri 1 Mollo Selatan. This research was carried out using quantitative analysis with a descriptive approach. The sample in this research was class XII IPS students, taken using nonprobability sampling techniques. Data collection techniques in this research were observation, questionnaires and documentation. Meanwhile the data in this study was analyzed using multipler linear regression. The result of the t test result of learning motivation (X1) are positive and significantly influencer learning difficulties significantly 0,000 < 0,05 thitung 8843 > 1,667 with ttable, parents attention (X2) are positive and significantly influencer lerning difficulties significance 0,000 < 0,05 thitung 6.761 > 1,667 ttable and teacher teaching methods (X3) are negatively and do not significantly influencer lerning difficulties significantly 0,078 > 0,05 thitung -1.792 > 1,667 ttable. Meanwhile the result of the F test (FHitung 83,622 > 2,74 Ftable )